Atributos biológicos e estoques de carbono e nitrogênio do solo em sistemas agropecuários no cerrado mineiro - Ana Clara Santos Duarte (2023)
Aiming to meet the goals related to the mitigation of climate change, stands out the important to study biological attributes, as well as carbon (C) and nitrogen (N) stocks, to assess the quality of soils cultivated with integrated production systems, mainly allied to the use of species that adapt to different edaphoclimatic conditions and have multiple uses in farming. Given the above, the objective was to evaluate the biological attributes and soil C and N stocks of different integrated production systems using Cratylia argentea in the Cerrado biome. Two experiments were carried out, being the experiment 1 consisting of 5 land uses: native vegetation (VN); conventional planting of maize (MAIZE); continuous pasture (PAST); cratylia integrated system + maize (CRAT); gliricidia integrated system + maize (GLIR). Experiment 2 was composed of 3 land uses: native vegetation (VN); continuous pasture (PAST); Cratylia integrated system + pasture (CRAT). Soil collection were carried out in two periods (December and July) to evaluate the following biological attributes: microbial biomass carbon (Cmic), microbial quotient (qMIC), labile carbon (CL), activity of urease and β-glucosidase enzymes, in the soil layers 0-5, 5-10 and 10-20 cm. Additionally, it was carried a soil collection out to determine total C and N, in layers 0-5, 5-10, 10-20, 20-30 cm. C contents and stocks were influenced by soil use, with higher averages observed in PAST. In experiment 1, the integrated systems showed higher soil C stocks compared to MAIZE. Already in experiment 2, the values were similar between PAST and CRAT. Soil quality biological attributes were influenced by management and sampling time. In experiment 1, the highest levels of Cmic and qMIC in the December evaluation were observed in PAST. In the July evaluation, urease enzyme activity and CL content were higher in the PAST, while β-glucosidase activity was higher in the GLIR system, followed by the CRAT system. In experiment 2, the highest contents of cmic, qMIC and β-glucosidase enzyme activity were observed for PAST and CRAT, in the two sampling times. Sustainable intensification systems using cratylia promoted improvements in soil quality, presenting potential for C accumulation and mitigation of greenhouse gas emissions.